Durabilidade mecânica de compósitos de polipropileno com reforço híbrido de fibra de coco e talco - Antunes, Marcela Caroline (Universidade Federal de São Carlos, 2012)
The use of natural fibers, as possible alternative reinforcement for synthetic fibers such as glass fibers, in polymer composites meets the requirement for development of new materials with environmentally sustainable technology. Such composites are especially attractive for engineering applications, such as in automobile industry, as these new materials can meet the requirements for adequate mechanical performance whilst exploiting the low density of natural fibers. As the mechanical fatigue durability is of fundamental importance in this area, the main objective of this work is to study the mechanical fatigue properties of polypropylene homopolymer (PP) composites with hybrid reinforcement of coconut fiber (CoF) and mineral filler talc (T), used to obtain a better balance between mechanical properties and lower density. Thus, PP composites with hybrid FCo/T reinforcement and compatibilized with maleated PP (PP-g-MAH) were prepared by twin-screw extrusion at various concentrations and test specimens injection molded for short-term mechanical properties characterization (tensile, flexural, impact and DMTA tests). The PP hybrid composite with the best balance of mechanical properties of stiffness, strength and reduced density was formulated with 30%FCo, 20%T and 3%PPg- MAH (wt %). This hybrid composite, along with its references composites with only FCo (30%) and only talc (20%), besides unmodified PP, were all submitted to fatigue testing carried out under cyclic sinusoidal tensile loading in tension controlled mode (frequency: 3 and 6 Hz and R = 0.1). The experimental results showed that all composites, both hybrid and reference composites, presented higher number of cycles to failure in comparison to the matrix PP polymer, probably due to reduction of mechanical hysteresis with increased content of reinforcement. However, extrapolation of the S-N fatigue curves indicates that all analyzed composites would present a fatigue resistance lower than the endurance limit observed for the unmodified PP polymer.
Durability mechanics of hybrid composites of Polypropylene reinforced with coconut fiber and talc
Keywords: Polímeros; Polipropileno; Reforço híbrido; Fibras naturais; Talco; Fadiga; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA